Illegal Utilization of National Identity Numbers by Political Parties during Elections - Puspita, Aisyah Rahmah; Ulya, Selma Lailatul (CV Era Digital Nusantara, 2024)
In this increasingly era importance technology information and data security , collection , processing and protection of personal data has become issue central in context democracy . For follow election , party political must through the registration and verification process carried out by the KPU via System Information Party Politics (Civil). Verification process This covers research and verification to required documents​ For become election participants . However Lots membership obtained​ For objective commercial with use Number Parent National Population (NIK), so give rise to problem . Policy privacy public in register and identify party political as participant election must ensure balance between need information party politics and protection privacy public . Rephrase Policy privacy national For registration and verification party political must capable create a fair , transparent and safe environment for all parties. Study This made For review study law about protection law in personal data security individuals whose personal data registered by political parties . Research methods used​ is normative and legal , use secondary and based data sources primary law . Findings study This show that Personal data protection is very important from corner look interest public and that enforcement Constitution personal data protection need consistent enforcement .​ Therefore​ that is , the law that regulates personal data protection in a way general Possible can help effort protection your law is in case This .